Mesoporous Perovskite Nanotube‐Array Enhanced Metallic‐State Platinum Dispersion for Low Temperature Propane Oxidation. Issue 10 (13th March 2018) - Wang, Sibo; Du, Shoucheng; Tang, Wenxiang; Hoang, Son; Lu, Xingxu; Xiao, Wen; Zhang, Bo; Weng, Junfei; Schneer, Evan; Guo, Yanbing; Ding, Jun; Zhang, Zhaoliang; et al.
Abstract: Plagued by low surface area and limited oxidation activity at low temperature, perovskite‐type LaMnO3 based catalysts also suffer from poor hydrothermal stability. In this communication, mesoporous nanotube arrays of LaMnO3 ‐Pt were successfully derived from core/shell nanorod arrays with significantly increased surface area through diluted acid etching. Surface Mn 4+ population is boosted to compensate La cation deficiency and enhance low temperature reducibility of nanotube arrays, enabling surface dispersion of abundant metallic‐state Pt nanoparticles. As a result, significantly enhanced catalytic propane oxidation was achieved in such a new class of perovskite/Pt nanotube array integrated structured catalysts. Abstract : Integrated monolithic catalysts : Mesoporous LaMnO3 ‐Pt nanotube arrays integrated structured catalysts were derived from core/shell nanorod arrays through diluted acid etching. It boosted the surface Mn 4+ population and enabed surface dispersion of abundant metallic‐state Pt nanoparticles, and enhanced catalytic hydrocarbons oxidation.